12th AIAA Aviation Technology, Integration, and Operations (ATIO) Conference and 14th AIAA/ISSMO Multidisciplinary Analysis And 2012
DOI: 10.2514/6.2012-5618
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Evaluation of Conflict Resolution and Weather Avoidance in Near-Term Mixed Equipage Datalink Operations

Abstract: The pilot-and controller-in-the-loop simulation described in this paper demonstrates the potential benefits of a near-term trajectory-based operations concept with datalink communications. Near-term operations with datalink are characterized by a fleet of which not all aircraft are equipped with datalink communications (i.e., mixed equipage). The objectives of this simulation were to continue to develop capabilities such as the conflict resolution algorithm, as well as evaluate new capabilities and concepts su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…ABMS has proven to be of great use in identifying emergent behavior in the complex socio-technical air transport system [12]. Key ABMS application examples are in non-nominal air traffic response to air traffic control instructions [13], network-wide air traffic delay analysis [14,15], agent-based safety risk analysis [16,17], and artificial phase transitions in air traffic [18]. However, to the best of the author's knowledge, using ABMS for gaining a better understanding of the role of coordination in the socio-technical air transport system is novel.…”
Section: Introductionmentioning
confidence: 99%
“…ABMS has proven to be of great use in identifying emergent behavior in the complex socio-technical air transport system [12]. Key ABMS application examples are in non-nominal air traffic response to air traffic control instructions [13], network-wide air traffic delay analysis [14,15], agent-based safety risk analysis [16,17], and artificial phase transitions in air traffic [18]. However, to the best of the author's knowledge, using ABMS for gaining a better understanding of the role of coordination in the socio-technical air transport system is novel.…”
Section: Introductionmentioning
confidence: 99%
“…CPDLC is operational in parts of Europe [13], and some operations have been conducted in the US [14,15]. Weather avoidance in a CPDLC datalink environment has been effectively demonstrated in pilot and controller in-the-loop simulations [16]. Any other means for the pilot to see a graphic display of the proposed route change with relevant weather and traffic, via Electronic Flight Bag automation for example, would likely help the flight crew and streamline the process [17].…”
Section: A Estimated Actual Savings Analysis Methodsmentioning
confidence: 99%
“…Its shorter-range counterpart, the Tactical Separation-Assured Flight Environment (TSAFE), operates on a time frame of 0 to 3 minutes. Human-in-the-loop simulations demonstrated that Autoresolver could be used simultaneously with TSAFE conflict detection 4 and/or TSAFE conflict resolution 5 as decision support tools for air traffic controllers in near-term operations. However, the interactions between these systems were not analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…15 In addition to this, a recent human-in the-loop simulation tested Autoresolver conflict detection and resolution and TSAFE conflict detection using three scenarios of 30-45 minutes each in 3 sectors of Fort Worth Center. 4 Post-simulation analysis of the 124 TSAFE alerts found that 14 were false alerts, with all but one involving at least one climbing flight. By comparison, this paper evaluates both systems in multi-Center (fast-time) simulations using 3 hours of aircraft takeoff data (about 4800 flights total).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation